PERSEPSI SISWA TERHADAP PELAKSANAAN PRAKTIK KERJA INDUSTRI SMK NEGERI 2 SUNGAI PENUH - 1605-1622 , Aman Kurnia Prayogi (Universitas Negeri Padang, 2016)
Abstract Industrial internship (prakerin) is one of collective program between vocational high school (SMK) and industries which is conducted in corporate world (DU/DI). Prakerin implementation at SMKN 2 Sungai Penuh is disharmony with prakerin implementation from other vocational high school, from the beginning of prakerin activities to the completion of final report. Based on this situation, this study is purposed to describe student’s perception to administration service, activities implementation, and supervisory of prakerin program at SMKN 2 Sungai Penuh. The type of this research is descriptive. This research is conducted for students of SMKN 2 Sungai Penuh in building engineering study program with total respondent of 47 students. Research finding shows that prakerin administration service in SMKN 2 Sungai Penuh is poorly implemented and unfits the guidance book, from 3 sub-indicator, one indicator is categorized as good, two other indicators is categorized as poor. Prakerin implementation at SMKN 2 Sungai Penuh is categorized as moderate for six sub-indicators that studied. Supervision is not implemented properly where two out of two indicators show poor supervision. Overall, it can be concluded that prakerin implementation at SMKN 2 Sungai Penuh is not performed properly. Keywords: perception, student, Prakerin.